Atomically Dispersed Dual-Metal Sites Showing Unique Reactivity and Dynamism for Electrocatalysis - Wu, Jun-Xi; Chen, Wen-Xing; He, Chun-Ting; Zheng, Kai; Zhuo, Lin-Ling; Zhao, Zhen-Hua; Zhang, Jie-Peng (Nano-micro letters, 2023)
Highlights An atomically dispersed catalyst with unprecedented N8V4 Co-Ni dual-metal sites is synthesized, which shows interesting asymmetric in situ structural evolution and serves as a quasi-bifunctional catalyst for water splitting. The flexible C–OH groups generated by in situ oxidation can reversibly turn on/off the hydrogen-bonding interaction with the oxygen evolution reaction intermediates to break the conventional scaling relationship. The real structure and in situ evolution of catalysts under working conditions are of paramount importance, especially for bifunctional electrocatalysis. Here, we report asymmetric structural evolution and dynamic hydrogen-bonding promotion mechanism of an atomically dispersed electrocatalyst. Pyrolysis of Co/Ni-doped MAF-4/ZIF-8 yielded nitrogen-doped porous carbons functionalized by atomically dispersed Co–Ni dual-metal sites with an unprecedented N8V4 structure, which can serve as an efficient bifunctional electrocatalyst for overall water splitting. More importantly, the electrocatalyst showed remarkable activation behavior due to the in situ oxidation of the carbon substrate to form C–OH groups. Density functional theory calculations suggested that the flexible C–OH groups can form reversible hydrogen bonds with the oxygen evolution reaction intermediates, giving a bridge between elementary reactions to break the conventional scaling relationship.